Imagined Communities: The Role of the Churches During and After Apartheid in Sophiatown - Mafuta, Willy (Université d'Ottawa / University of Ottawa, 2016)
Many around the world have come to know South Africa as the rainbow nation, yet this notion has been subject to enormous critiques in the political discourse. The rainbow nation was conceived by the Government of National Unity that came to power in 1994, but it failed to materialize. What post-apartheid South Africa has yielded instead is a nation, or an imagined community, where race and ethnicity never receded. Although they are no longer pathological, race and ethnicity have become normative typifications of an overarching identity. Churches in particular have played a major role in creating a new identity. Churches have managed to move beyond the yoke of race and ethnicity enforced during the Apartheid under the Group Areas Act and the Resettlement Acts, and epitomized by the destruction of the vibrant city of Sophiatown and, in its place, the building of Triomf, an Afrikaner imagined community. Churches have led the way in deconstructing the perceived or realized power or disempowerment that is residual to the Apartheid. In reconstructing the community, they have re-imagined an environment where race and ethnicity remain the standard component of the South African national identity. This re-imagining requires that race and ethnicity be constructed as relational rather than hierarchical. Moreover, it requires that one acknowledge the woundedness (e.g., shame, anger, guilt, hurt, humiliation, betrayal, fear, resentment) that racial typifications create. As a social construction, Churches in Sophiatown are fostering this ethical environment where these values are embraced.
Keywords: Identity Politics; Dutch Reformed Church; African Independent Churches; Race and Ethnicity in south Africa; South Africa Post-Apartheid; Role of the Churches; Rainbow Nation; Group Area Act; Group Resettlement Act; Sophiatown; Triomf; Trevor Huddleston